Key to world Stictothrips species with description of a new species from Iran (Thysanoptera: Phlaeothripidae) - Minaei, Kambiz; Mound, Laurence (Zootaxa, 2020)
An illustrated key is provided to distinguish seven species of the genus Stictothrips Hood. Information is provided concerning the distribution and variation among these fungus-feeding thrips, and a new species of the genus, S. denaeus sp. n., is described from both sexes collected in Kohgiluyeh and Boyer-Ahmad province, south-west of Iran.